Study from the United States: increased prevalence of kidney stones in patients with high weight-adjusted waist index - Gui, Zhaohua; Yu, Longshan; Chen, Yan; Zhang, Mingxun; He, Jie; Hao, Yunwu (Frontiers in Nutrition, 2024)
Objective Using data from NHANES 2007–2018, to examine the association between WWI (weight-adjusted waist index) index and prevalence of kidney stones. Methods Using multiple logistic regression analysis of the National Health and Nutrition Examination Survey (NHANES) 2007–2018, we evaluated the association between WWI index and the prevalence of kidney stones, followed by subgroup analysis of sensitive populations. Smooth curve fitting was used to determine whether there was a non-linear relationship between the WWI index and kidney stone prevalence, and threshold effect analysis was used to test this relationship. Results Among 29,280 participants, 2,760 self-reported renal calculi. After adjustment for all confounders, there was a positive association between WWI and kidney stone prevalence (OR = 1.20, 95% CI: 1.12, 1.28), and this positive association was stronger with increasing WWI (and P = 0.01 for trend). Our results indicate a non-linear positive correlation between WWI index and kidney stones, with the saturation threshold effect analysis and the most important threshold value at 11.02. According to subgroup analysis, WWI showed the strongest association with kidney stone prevalence in participants aged 20–39 years, males, other US ethnic groups, and participants without hypertension and diabetes. Conclusion Increased WWI is positively associated with increased incidence of kidney stones, and increased WWI is a high risk for kidney stones that should be treated with caution. This association should be more pronounced in people between the ages of 20 and 39 years, in men, in other US ethnic populations, and in participants who do not have hypertension or diabetes.